Brincando com os orixás: ser criança no candomblé - Ribeiro, Adele Cristiane dos Reis Generoso (2017)
The propose of this research is to check and realize children’s role at Guarulhos’ candomblé, at the beginning of XXI century. It is an historical study that, from documentary’s unfolding Brincando com os deuses, nine protagonists children’s actions, were analyzes the themes developed in the documentary such as orixás, body e death. With the theoretical methodological contribution of oral history and ethno history, was related the children's play expressed in the documentary to the Yoruba philosophy and it was noticed that they are not prior to adult life but rather activities aimed at understanding the universe they live and propose ways of reinforcing and reflecting the actions of candomblé’s philosophy. Around this, the inherent hierarchy of candomblé was identified and it was perceived that there is a tenuous limit between the carnal family and the family of faith, since both have propositions of important values for the construction of the human being, which are understood in the dissertation as complementary families in order to maintain the care and protection of the community in candomblé. Thus, motherhood is also problematized in the dimensions of religion and corroborates the understanding of the roles of children in candomblé. Also stands out orikis and itã for perception of the figure of the children in these pedagogies of candomblé. Both representations of figures of the children and the representations that the children possess, activate playfulness and wisdom to the understanding of the dimension of candomblé. But as these dimensions are not yet understood in secular society, research also shows which vision children have about religious discrimination and racism